MASKULINITAS YANG FEMININ PADA SOSOK AYAH DALAM LIRIK LAGU VIRGOUN “Saat Kau Telah Mengerti” - Rane, Zakridatul Agusmaniar (Seshiski: Southeast Journal of Language and Literary Studies, 2023)
This study analyzed the characteristics of father masculinity as represented in the lyrics of Virgoun’s song "Saat Kau Telah Mengerti". The lyric describes father as a strict, firm and leading figure. But the expression of his feeling to his child describes his feminine side. A father seems to have a unique masculinity. The data was obtained by transcribing Virgoun’s song "Saat Kau Telah Mengerti" and then analyzed it using Van Dijk's critical discourse analysis. The results of the study found that father’s masculinity is different from what is required by hegemonic masculinity of patriarchal society. Hegemonic masculinity defines a man as the one who is free from feminine traits. In this lyric, father is a man with dual roles as husband and parent. It gives him a feminine masculinity. As the head of the family, he constructs a tough, assertive, and domineering attitude. While the fact that he is a parent instills a sense of affection, love, and the desire of caring children. masculine and feminine traits negotiated within him. His strict attitude is not merely the manifestation of masculine traits required by gender discourse, but an attitude driven by love for his child. Femininity infiltrates his masculinity and coexist within him.